Pengaruh Literasi Ekonomi Dan Kontrol Diri Dalam Penggunaan E-Commerce Terhadap Impulsive Buying Pada Siswa SMA - Putri Rifaatul Mahmudah; Heni Purwa Pamungkas (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of economic literacy and self-control in e-commerce use on impulsive buying in high school students. The sample was 10th-grade students at SMAN 18 Surabaya, with a total of 156 respondents selected using proportional random sampling. This study used a quantitative approach with a survey method. The research instruments consisted of tests and questionnaires that had been tested for validity and reliability. Data analysis used multiple linear regression with the help of IBM SPSS Statistics version 25 software. The results showed that economic literacy had a negative and significant effect on impulsive buying. This indicates that the higher a student's economic literacy, the lower their tendency to engage in impulsive buying. Furthermore, self-control in e-commerce use also has a negative and significant effect on impulsive buying. This suggests that students who are able to control themselves when using e-commerce are less likely to be tempted to engage in impulsive buying. Simultaneously, economic literacy and self-control in e-commerce use significantly influence impulsive buying, with a fairly strong contribution in explaining variations in impulsive buying behavior among adolescents. Keywords: Economic Literacy, Self-Control, E-Commerce, Impulsive Buying, High School Students